2013
DOI: 10.1124/jpet.112.201863
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Ameliorates Chemically Induced Colitis in the Mouse through Modulation of a PXR/NF-κB Signaling Pathway

Abstract: Targeted activation of pregnane X receptor (PXR) in recent years has become a therapeutic strategy for inflammatory bowel disease. Chrysin is a naturally occurring flavonoid with antiinflammation activity. The current study investigated the role of chrysin as a putative mouse PXR agonist in preventing experimental colitis. Pre-administration of chrysin ameliorated inflammatory symptoms in mouse models of colitis (dextran sodium sulfate-and 2,4,6-trinitrobenzene sulfonic acid-induced) and resulted in down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 26 publications
4
71
0
Order By: Relevance
“…We, and others, have reported previously that the PXR plays an important role in maintaining intestinal mucosal homeostasis (Zhou et al, 2006;Terc et al, 2014;Venkatesh et al, 2014), and its activation dampens inflammation and mucosal damage in experimental colitis Shah et al, 2007;Dou et al, 2012Dou et al, , 2013Dou et al, , 2014Terc et al, 2014). In our previous report, we found that treating mice with PCN attenuated colonic mucosal neutrophil infiltration and afforded barrier protection (Terc et al, 2014).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We, and others, have reported previously that the PXR plays an important role in maintaining intestinal mucosal homeostasis (Zhou et al, 2006;Terc et al, 2014;Venkatesh et al, 2014), and its activation dampens inflammation and mucosal damage in experimental colitis Shah et al, 2007;Dou et al, 2012Dou et al, , 2013Dou et al, , 2014Terc et al, 2014). In our previous report, we found that treating mice with PCN attenuated colonic mucosal neutrophil infiltration and afforded barrier protection (Terc et al, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…Highly expressed in the liver and intestinal epithelium, the PXR has been previously characterized as a master regulator of xenobiotic metabolism and clearance (Watkins et al, 2002;Staudinger et al, 2006;Shukla et al, 2011;Dou et al, 2013;Pondugula and Mani, 2013). Acting as a sensor of exogenous chemicals, the PXR's activation leads to the expression of a variety of target genes related to detoxification and efflux pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following measurement of the colon length, the distal colon was taken and fixed in 10% (wt/vol) buffered formalin for H&E staining. Histological damage was assessed as a combined score of inflammatory cell infiltration (score 0 -3) and mucosal damage (score 0 -3) by a method previously described (5,24,36). For inflammatory cell infiltration in the colon mucosa, rare inflammatory cells (mononuclear infiltrates) in the lamina propria were counted as 0; increased numbers of inflammatory cells, including neutrophils in the lamina propria, were counted as 1; confluence of inflammatory cells, extending into the submucosa, were scored as 2; and a score of 3 was given for transmural extension of the inflammatory cell infiltration.…”
Section: Methodsmentioning
confidence: 99%
“…DSS or trinitrobenzene sulfonic acid (TNBS) colitis was induced in mice as described previously (Dou et al, 2012(Dou et al, , 2013b. In brief, 4% (w/v) DSS (molecular mass 36-50 kDa; MP Biomedicals, Solon, OH) was administered in the drinking water (tap water) for 7 days, whereas control mice received tap water only (n 5 10 mice in each group).…”
Section: Groupmentioning
confidence: 99%